HARDINESS AS A RESOURCE FOR CONSTRUCTIVE BEHAVIOR IN CONFLICT SITUATIONS AMONG PSYCHOLOGY STUDENTS - Nurymbetova, Elmira Jumamuratovna (SCIENCE and SOCIETY, 2026)
The article examines conflict behavior and hardiness among psychology students. Indicators of involvement, control, risk acceptance, and conflict resolution strategies are analyzed. The findings emphasize the importance of developing personal resources for the professional growth of future psychologists.
Keywords: hardiness; conflict behavior; involvement; control; risk acceptance; psychology students; professional training